Răspuns:
21 − [a + (a : 3 + 4) + a] = a : 2
21 − a - (a : 3 + 4) - a = a : 2
21 - 2a - a : 3 - 4 = a : 2
2a + a : 2 + a : 3 = 17 |×6
12a + 3a + 2a = 102
17a = 102
[tex]a = 102 : 17[/tex]
a = 6
sau:
21 − [a + (a : 3 + 4) + a] = a : 2 |×2
42 - 2[a + (a : 3 + 4) + a] = a
a + 2[a + (a : 3 + 4) + a] = 42
a + 2a + 2(a : 3 + 4) + 2a = 42
5a + 2(a : 3 + 4) = 42
5a + 2 × a : 3 + 8 = 42
5a + 2 × a : 3 = 42 - 8 = 34
5a + 2 × a : 3 = 34 |×3
15a + 2 × a : 3 × 3 = 102
15a + 2a = 102
17a = 102
a = 102 : 17
a = 6